Candida albicans and Candida glabrata sharing a live in vaginal environment - Silva, Sónia Carina (2014)
Candidal vulvovaginitis (CV) is an infection of the mucous membranes of the vagina by Candida . Up to 75% of woman will have this infection at same point in their lives and approximately 5% will have recurring episodes. Candida species are found naturally in the vagina, and are usually harmless. However, conditions in the vagina may change resulting in an environment that facilitates Candida infection. However, it remains unclear what specific changes in the vaginal environment, or amongst the Candida , are key to promoting CV. The current study examined the interaction and expression of virulence factors by two frequent Candida species colonising the vagina, namely Candidaalbicans and C. glabrata. In vitro infection studies were performed using a reconstituted human vaginal epithelium (RHVE), which facilitated examining the effect of altered environmental factors on Candida virulence. Confocal laser scanning microscopy showed that in single species infection, C. albicans was an extensive colonizer and invader of the RHVE, which was in direct contrast to C. glabrata . However, increased colonization and invasion of the RHVE by C. glabrata was evident in dual species infection. Furthermore, in dual species infection, expression of the C. glabrata epithelial adhesin (EPA) family of genes was considered less relevant to the infection process than expression of C. albicans virulence genes ( HWP1; ALS and Phospholipases B and D family). Interestingly, up- regulation of ALS 3 and HWP1 by C. albicans was evident in dual species infection. When the vaginal environment was modified by changing like pH or increasing progesterone concentration, decreased RHVE colonization by both species occurred together with reduced hyphal production by C. albicans and down regulation of HWP1. In conclusion, this work demonstrated that dual species infection of RHVE results in enhanced pathogenicity, which in turn, is attenuated by environmental changes.